2021
DOI: 10.3390/ijms22083832
|View full text |Cite
|
Sign up to set email alerts
|

Challenges on Cyclic Nucleotide Phosphodiesterases Imaging with Positron Emission Tomography: Novel Radioligands and (Pre-)Clinical Insights since 2016

Abstract: Cyclic nucleotide phosphodiesterases (PDEs) represent one of the key targets in the research field of intracellular signaling related to the second messenger molecules cyclic adenosine monophosphate (cAMP) and/or cyclic guanosine monophosphate (cGMP). Hence, non-invasive imaging of this enzyme class by positron emission tomography (PET) using appropriate isoform-selective PDE radioligands is gaining importance. This methodology enables the in vivo diagnosis and staging of numerous diseases associated with alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 163 publications
(597 reference statements)
0
2
0
Order By: Relevance
“…Positron emission tomography (PET) is a molecular imaging technique that allows quantification of biochemical targets and processes in vivo. PET can be valuable in preclinical and clinical drug development because it can provide critical information about target engagement and occupancy by a drug candidate under specific dose regimens. , The development of radioligands for PET imaging of various PDE enzymes is an active area of research that has provided significant advances for imaging PDEs in families 2, 5, 7, and 4. , At a few research institutes, PDE4 has been imaged in human subjects with PET using the pan-subtype-selective radioligand [ 11 C]­( R )-rolipram. A PDE4B-prefering PET radioligand, code-named [ 18 F]­PF-06445974, has been developed recently and applied in human study. However, so far, there is no successful PDE4D-selective radioligand. Recently, we have been seeking to develop PDE4D subtype-selective PET radioligands.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) is a molecular imaging technique that allows quantification of biochemical targets and processes in vivo. PET can be valuable in preclinical and clinical drug development because it can provide critical information about target engagement and occupancy by a drug candidate under specific dose regimens. , The development of radioligands for PET imaging of various PDE enzymes is an active area of research that has provided significant advances for imaging PDEs in families 2, 5, 7, and 4. , At a few research institutes, PDE4 has been imaged in human subjects with PET using the pan-subtype-selective radioligand [ 11 C]­( R )-rolipram. A PDE4B-prefering PET radioligand, code-named [ 18 F]­PF-06445974, has been developed recently and applied in human study. However, so far, there is no successful PDE4D-selective radioligand. Recently, we have been seeking to develop PDE4D subtype-selective PET radioligands.…”
Section: Introductionmentioning
confidence: 99%
“…So far, all intentions to develop PDE2A specific radiopharmaceuticals are on the basis of PDE-targeted therapeutics with low-molecular weight mainly acting as inhibitors via binding to the substrate binding pocket at the catalytic site of the enzymes [ 1 , 13 , 14 ]. In brief, despite numerous efforts during the last years, the imidazolotriazine derivative [ 18 F]PF-05270430 remains so far the most advanced tracer with preclinical and first in human studies reported already in 2016 [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%